PROCEDURAL SUCCESS AND IMMEDIATE POST-PROCEDURE COMPLICATIONS OF PERCUTANEOUS TRANSVENOUS MITRAL COMMISSUROTOMY IN PATIENTS WITH RHEUMATIC MITRAL STENOSIS AT A TERTIARY CARE CENTER - DURRANI, T; NASIR , H; ASMA, S; HUSSAIN, I; AZIZ, S; GUL, S (Biological and Clinical Sciences Research Journal, 2023)
Percutaneous Transvenous Mitral Commissurotomy (PTMC) is a minimally invasive procedure for mitral stenosis. Successful PTMC is achieving a post-procedural mitral valve area (MVA) of ≥1.5 cm2 with echocardiographic mitral regurgitation of less than grade 3–4 post-PTMC. Objectives: The study’s main objective is to assess the Procedural success and Immediate post-procedure Complications like worsening pre-existing mild MR (1) or development of new mitral regurgitation (2) and embolic stroke after the percutaneous transvenous mitral commissurotomy. Methods: This study aimed to evaluate the procedural success of PTMC in patients with mitral stenosis at Hayatabad Medical Complex, Peshawar, from January 2021 to June 2021. Pre-procedure transthoracic echocardiography was performed to determine the mitral valve area, pulmonary artery systolic pressure, trans-mitral pressure gradient, and the presence and severity of mitral regurgitation (MR). The mitral valve area was calculated through planimetry, while the pulmonary artery systolic pressure was measured using Doppler Echo. Results: The mean age of the patients was 42.7 ± 11.5 years, with 23 (28.75%) males and 57 (71.25%) females. The mean mitral valve area before PTMC was 0.97 ± 0.18 cm2, which increased to 1.62 ± 0.17 cm2 after the procedure, and this increase was statistically significant (p=<0.001). The post-PTMC MVA varied with PTMC Wilkin's score, with scores less than or equal to 8 have favorable outcomes. Immediate post-procedure complications were also studied, according to which only 3 (3.75%) out of 80 patients had more than mild MR and none had stroke or TIA. The study concludes that PTMC is an effective and safe treatment option for patients with mitral stenosis, having a favorable Wilkin’s score, resulting in a significant increase in MVA after the procedure. After PTMC, there were mostly minor complications immediately after the procedure that were treated conservatively with good results. Further studies are needed to evaluate the long-term outcomes of PTMC in larger patient populations.